Real-time health monitoring via ECG analysis - Budichenko, V.O.; Panchenko, T.V. (Штучний інтелект, 2016)
In this paper we describe the range of use cases of medical wearable IoT devices for monitoring health state in real-time. We propose approaches for analysis the dynamic analogous but digitized electrocardiogram in combination with other personal data like age, gender, medical card and some sensors like GPS and accelerometer by neural network or some other machine learning method. It should be trained on classified dataset and then be adjusted for specific person to monitor and classify in real-time his or her health state whether he or she is healthy or if some abnormality detected. This paper is the declaration of our research and its development which is at the data gathering and preparation stage.